Work Posture Analysis with Rapid Entire Body Assessment (REBA) Method on Production Operators At PT. Prestasi Ide Jaya Mojokerto - Rusindiyanto; Rizqi Novita Sari; Aditya Yusuf Indrastana (Nusantara Science and Technology Proceedings)
Heavy workload and non-ergonomic facility layout design will result in the excessive labor force and wrong body position. PT. Prestasi Ide Jaya produces slippers and Eva sponges. Eva sponge is the base used in the manufacture of soles or parts of sandals. From the observations that have been made on the production floor of slippers and Eva sponges, there are still non-ergonomic production operator activities, namely in the mixing, cutting, and packing processes. The objectives to be achieved in this study are to improve the position of production operators in the company using the Rapid Entire Body Assessment (REBA) method and provide suggestions for improving work postures and facilities by the results of the posture assessment using the Rapid Entire Body Assessment (REBA) method. The results of the study stated that the insole screen printing section workers got a category five score, the plong cutting section workers got a category seven score, the flip-flops assembly section workers got a category five score, the finishing section workers got a category five score, and the packing section workers got a category five score. All scores can be interpreted as a moderate level of risk and require preventive action.